A high-Q, high-sensitivity refractive index sensor based on abundant defective modes of a 12-fold quasiperiodic photonic crystal. (2nd December 2019) - Zhou, Lin; Cui, Ting; Feng, Shuai; Zhang, Xiaoming; Li, Chuanbo; Guo, Honglian
Abstract: The refractive index-sensing characteristics of the defective modes of a 12-fold quasiperiodic photonic crystal are studied. The proposed structure is composed of silicon rods immersed in a free-flowing liquid environment, which is convenient for achieving real-time detection. The refractive index sensitivity of our proposed structure is about 894 nm per refractive index unit (RIU) for near-infrared wavelengths around 1550 nm, and the limit of detection is 8.75  ×  10 −5 RIU. The influence of the thickness of protein attached to the silicon columns on the shift and transmittance of the resonant wavelengths is also studied: the quality factor of the resonant peak is more than 1.2  ×  10 5, and a minimum variation in protein thickness of less than 5 nm can be distinguished by optimizing the size of the central column.